Efisiensi Energi Sistem Operasi Mobile Menggunakan Chip Cheetah X1 Infinix - Rakhmadi Rahman; Fadhil Aditya; Meiana Sahabuddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This journal discusses the energy efficiency of mobile operating systems using the Infinix Cheetah X1 chip. The study evaluates the chips’s ability to manage power consumption without compromising performance, focusing on battery optimization, charging performance under extreme temperatures, and bypass charging tecnology. Empirical testing on the Infinix Note 40 using tools like CPU-Z and 3C Battery Manager shows that the Cheetah X1 chip enhances charging efficiency and maintains optimal device temperature. However, its impact on overall battery life is minimal, demonstrating normal power cusumpition levels for a smartphone with a 5000 mAh battery. Overall, the chip improves user experiences through innovative charging features and effective power management, although its effect on extending battery life is limited.